A mini-review of three-dimensional network topological structure nanocomposites: Preparation and mechanical properties - Liu Yusong (De Gruyter, 2021)
Three-dimensional (3D) network topological structure composite (3D-NTSC) is a new type of composite in which both the matrix phase and the reinforced phase have 3D continuous network structure and interweave with each other. Different from fiber reinforcement and particle reinforcement, the reinforcing phase in the composite material runs through the whole matrix phase in a continuous form without destroying the topological continuity of the matrix phase, so that each matrix phase in the composite material can not only maintain its own excellent performance, but also can cooperate with each other and complement each other, so that the composite material can play a greater performance advantage. In recent years, 3D-NTSC has attracted the attention of researchers and has been widely used in practical production. At present, there are no comprehensive articles summarizing the research progress of this kind of materials. In this review, we discussed the recent progress of the preparation methods, including natural flow method, vacuum infiltration process, pressure filling method, in situ filling method, and co-building method. Furthermore, research progress on mechanical properties and some regular results, shortcomings, challenges, and prospects of 3D-NTSC were also put forward, which would be helpful to people working in the related fields.